Sustainable nature tourism transformation: The strategic role of green tourism in West Java - Setiadi, Sandi; Widyastuti, Sri; Zulkifli, Zulkifli; Darmansyah, Darmansyah (Edelweiss Applied Science and Technology, 2025)
This study examines the role of Green Marketing, Social Media, Destination Image, and Tourist Perception on Green Tourism and Sustainability in West Java. This study uses quantitative research methods. It was conducted in a natural tourism area where there are 355 natural attractions in West Java, which are divided into two types of environmental services: 205 forest areas and 150 places outside the forest area. The results of the analysis show that Green Marketing has no effect on Green Tourism and Sustainability due to low tourist awareness. On the other hand, Social Media and Destination Image contribute positively by increasing tourist awareness of sustainable tourism. Tourist Perception has no direct effect, indicating that understanding alone is not enough to encourage real action. Green Tourism contributes significantly to Sustainability through conservation, education, and resource management. This study emphasizes the importance of effective marketing strategies and the role of social media in encouraging tourists to behave more responsibly.